2018
DOI: 10.3892/ol.2018.8973
|View full text |Cite
|
Sign up to set email alerts
|

Thymidylate synthase predicts poor response to pemetrexed chemotherapy in patients with advanced breast cancer

Abstract: Pemetrexed is a candidate chemotherapy regimen for anthracycline- and taxane-pretreated advanced breast cancer. However, to the best of our knowledge, no efficient treatment efficacy biomarkers have been identified. In the present study, the potential correlation between thymidylate synthase (TYMS) expression and clinical response to pemetrexed was examined in advanced breast cancer. A retrospective collection was performed by using 77 advanced breast cancer subjects, who received at least three cycles of peme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…We also found that patients with AL with relapse showed increased mRNA expression levels of TS. Our results are in line with previous reports showing a significant aggressive phenotype and poor prognosis (47–49). These data indicate that TS is involved in disease progression and relapse in cancer, which occur because TS is a target enzyme of MTXPG and is overexpressed in AL and in patients with relapse.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We also found that patients with AL with relapse showed increased mRNA expression levels of TS. Our results are in line with previous reports showing a significant aggressive phenotype and poor prognosis (47–49). These data indicate that TS is involved in disease progression and relapse in cancer, which occur because TS is a target enzyme of MTXPG and is overexpressed in AL and in patients with relapse.…”
Section: Discussionsupporting
confidence: 94%
“…TS is a folate-dependent enzyme that plays a central role in deoxythymidine monophosphate synthesis, which is critical for the synthesis and repair of DNA by serving as the main intracellular source of dUTM (46,47). Our results show increased levels of TS mRNA in patients with AL, similar to findings observed in breast cancer (47) and pancreatic cancer (20). We also found that patients with AL with relapse showed increased mRNA expression levels of TS.…”
Section: Discussionmentioning
confidence: 99%
“…TUBB3 is thought to be a marker of taxane resistance, and high expression levels of TUBB3 are reported to correlate with low response rates in patients treated with taxane-containing regimens (8,9). The expression level of TYMS, which is a central enzyme in the folate metabolic pathway and a major target for cytotoxic antifolate chemotherapeutic agents, such as 5-fluorouracil and capecitabine, is negatively associated with the efficacy of antimetabolic drugs (10,11). TOP2A is an essential nuclear enzyme that changes DNA topology and is the primary molecular target of various cytotoxic agents, including anthracyclines.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Additionally, TYMS polymorphisms may predict the chemosensitivity to 5-fluorouracil, doxorubicin, cyclophosphamide, pemetrexed and so on. [20,21,9] TYMS SNPs influence cancer susceptibility and chemosensitivity via effects on TYMS expression [22] and its effects differ with respect to race. [23,11] However, inconsistent results have been obtained regarding the association between the miRNA binding sites of TYMS SNPs and breast cancer and data from Asian populations are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…[5] As a proliferation marker, TYMS expression may be related to pathological complete response (pCR) rates in triple-negative breast cancer (TNBC). [7] Furthermore, TYMS is used to predict chemosensitivity [6,9] and trastuzumab resistance [10].…”
Section: Introductionmentioning
confidence: 99%